Block copolystyrene derivatives having flexible alkylsulfonated side chains and hydrophobic alkoxy chains as a proton exchange membrane for fuel cell application. Issue 10 (19th February 2013) - Sheng, Li; Higashihara, Tomoya; Maeda, Rina; Hayakawa, Teruaki; Ueda, Mitsuru
Abstract A series of block copolystyrene derivatives, poly[4‐(4‐sulfobutyloxy)styrene]x‐block‐[4‐(n‐butoxystyrene)]y (PSBOSx‐b‐PnBOSy), containing a flexible alkylsufonated side chain and hydrophobic alkoxy chain with various ion exchange capacities (IECs) have been synthesized based on living anionic polymerization. The resulting crosslinked membranes were prepared using 4, 4′‐methylene‐bis[2, 6‐bis(hydroxyethyl)phenol] as the crosslinker in the presence of methanesulfonic acid. The crosslinked PSBOS2.2‐b‐PnBOS1 membrane with IEC of 2.89 mequiv g−1 displays a high proton conductivity (0.01 S cm−1) at 30% relative humidity and 80 °C, which is comparable to that of Nafion. The well‐developed phase separation and the continuous hydrophilic domains in the crosslinked PSBOS2.2‐b‐PnBOS1 membranes have been observed in a transmission electron microscope image. Moreover, the dynamic mechanical analysis measurement and Fenton's reagent testing show that the crosslinked PSBOSx‐b‐PnBOSy membranes have good mechanical properties and oxidative stability. These results indicate that the introduction of flexible alkylsulfonated side chains to the polystyrene main chains positively affect both the proton conductivity and oxidative stability. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013